1988
DOI: 10.1111/j.1532-5415.1988.tb03434.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Failure in the Aged: Evaluation and Treatment

Abstract: With aging, there are changes in both libido and erectile function. Although the majority of aged men remain interested in sex, less than 15% report continued sexual intercourse. The cause of this "libido-potency gap" is due primarily to erectile failure. Penile erection is dependent upon a complex interaction of the autonomic nervous system, cardiovascular system, and local neurotransmitters such as acetylcholine and vasoactive intestinal polypeptide. Sexual stimulation causes augmented blood flow into the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Each subject was asked to answer the question as if he or she were the patient in question in the scenario. To control for patient assumptions about what state of mental or physical health they would be in during and after either treatment, all patients were told that (1) their quality of life with each treatment would be the same except for the data (mortality risk) shown in the curves, and (2) their level of mental and physical functioning would be minimally compromised by either treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each subject was asked to answer the question as if he or she were the patient in question in the scenario. To control for patient assumptions about what state of mental or physical health they would be in during and after either treatment, all patients were told that (1) their quality of life with each treatment would be the same except for the data (mortality risk) shown in the curves, and (2) their level of mental and physical functioning would be minimally compromised by either treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The investigator reviewed each curve with each patient identifying: (1) the x‐ and y‐axes of the graph and (2) the labels of the axes and their units of measurement. The investigator then directed each patient's attention to the curves and reviewed each curve individually with the patient as follows: (1) identifying the year‐0 point as the point at which the data were summarized for how many patients were still alive and already dead during treatment and the peri‐treatment period; (2) tracing down the length of each curve and noting the time‐point at which it crossed the other curve and the number of patients still alive and already dead at the cross‐over point; and (3) identifying the 5‐year data point on each curve and noting the number of patients still alive and the number dead. Patients were told survival information beyond year 5 was not available for either treatment group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual dysfunction (primarily erectile failure) may be the most common health disorder to afflict aged males 1 . Diagnostic and therapeutic approaches to erectile sexual dysfunction have been delineated, 2 but Slag et al 3 reported that 50% of men with erectile dysfunction are not interested in pursuing evaluation. Therefore, other factors beyond erectile failure must account for why only a subset of dysfunctional men seek evaluation.…”
mentioning
confidence: 99%